Patterns of genomic and phenomic diversity in wine and table grapes. (2nd August 2017) - Migicovsky, Zoë; Sawler, Jason; Gardner, Kyle M; Aradhya, Mallikarjuna K; Prins, Bernard H; Schwaninger, Heidi R; Bustamante, Carlos D; Buckler, Edward S; Zhong, Gan-Yuan; Brown, Patrick J; Myles, Sean
Abstract: Grapes are one of the most economically and culturally important crops worldwide, and they have been bred for both winemaking and fresh consumption. Here we evaluate patterns of diversity across 33 phenotypes collected over a 17-year period from 580 table and wine grape accessions that belong to one of the world's largest grape gene banks, the grape germplasm collection of the United States Department of Agriculture. We find that phenological events throughout the growing season are correlated, and quantify the marked difference in size between table and wine grapes. By pairing publicly available historical phenotype data with genome-wide polymorphism data, we identify large effect loci controlling traits that have been targeted during domestication and breeding, including hermaphroditism, lighter skin pigmentation and muscat aroma. Breeding for larger berries in table grapes was traditionally concentrated in geographic regions where Islam predominates and alcohol was prohibited, whereas wine grapes retained the ancestral smaller size that is more desirable for winemaking in predominantly Christian regions. We uncover a novel locus with a suggestive association with berry size that harbors a signature of positive selection for larger berries. Our results suggest that religious rules concerning alcohol consumption have had a marked impact on patterns of phenomic and genomic diversity in grapes. Abstract : Grape breeding: Edible to the east, wine to the west Genetic and morphological analyses suggest that distinct classes of wine and table grapes developed in different parts of the world. Grape breeding is hampered by the delay before desirable characters, such as fruit quality, become visible. A US-Canadian team led by Sean Myles of Dalhousie University, Truro, Canada, addressed this problem using historical descriptions held alongside genetic material in one of the world's largest gene banks, the USDA germplasm collection. Grapes from eastern, predominantly alcohol-abstaining Islamic countries tended to be larger, firmer, and widely spaced: ideal characteristics for table varieties. In western, predominantly Christian areas, grapes were smaller and densely clustered, with higher sugar and acidity levels, more suitable for wine-making. The team explored the genetic differences underpinning this variation, giving a greater understanding of the complex domestication history of this economically important crop.